Revitalization And Activation of Rural Areas on The Example of An Association of Activities in Poland - Igor POGONOWSKI; Małgorzata BŁAZEJOWSKA (Communications of International Proceedings, 2023)
Purpose:The purpose of the article is to show the importance of a non-governmental organization in the revitalization of rural areas and activation of the local community on the example of the activity of the Henrykowski Association in Siemczyno in Poland. Design/Methodology/Approach:The research method is a descriptive analysis of the selected example on the basis of a detailed verification of legal documents related to the functioning of the entity - acts and registration documents. Findings:The results of the study show that the association operates in rural areas and initiates many cultural, educational and environmental events. The organization promotes the history and culture of the region by publishing cyclical "Notebooks of  Siemczyńsko - Henrykowski". The dynamic activity of the association led to the revitalization of the palace complex, which became the center of cultural and historical events for the local community, and a tourist attraction with an interactive museum of baroque and a universal of various crafts.  Practical Implications:The most important practical implication is that the activity of the association has significantly influenced local development. It contributed to the revitalization of the rural area and the activation of the inhabitants. The described achievements may be an inspiration for other communes where there are neglected historical buildings.
Keywords: local development; revitalization; activation; association